HIV, HCMV and mycobacterial antibody levels: a cross‐sectional study in a rural Ugandan cohort. Issue 2 (27th December 2018) - Stockdale, Lisa; Nash, Stephen; Nalwoga, Angela; Gibson, Lorna; Painter, Hannah; Raynes, John; Asiki, Gershim; Newton, Robert; Fletcher, Helen
Abstract: Objectives: A growing evidence base implicates human cytomegalovirus (HCMV) as a risk factor for TB disease. We investigated total IgG and mycobacteria‐specific antibodies in a cross‐sectional study nested within a rural Ugandan General Population Cohort (GPC), in relation to HIV infection and the magnitude of HCMV IgG response. Methods: Sera from 2189 individuals (including 27 sputum‐positive TB cases) were analysed for antibodies against mycobacteria (Ag85A, PPD, LAM, ESAT6/CFP10) and HCMV, tetanus toxoid (TT) and total IgG. Results: Anti‐mycobacterial antibodies increased with age until approximately 20 years, when they plateaued. Higher HCMV exposure (measured by IgG) was associated with lower levels of some anti‐mycobacterial antibodies, but no increase in total IgG. HIV infection was associated with a decrease in all anti‐mycobacterial antibodies measured and with an increase in total IgG. Conclusions: The increase in anti‐mycobacterial antibodies with age suggests increasing exposure to non‐tuberculous mycobacteria (NTM), and to M.tb itself. HIV infection is associated with decreased levels of all mycobacterial antibodies studied here, and high levels of HCMV IgG are associated with decreased levels of some mycobacterial antibodies. These findings point towards the importance of humoral immune responses in HIV/TB co‐infection and highlight a possible role of HCMV as a risk factor for TB disease.